Southwest monsoon rainfall in India : Part II - Principal components in temporal domain - MAZUMDAR, A. B. (MAUSAM, 1998)
An attempt has been made towards objective identification of phases of the southwest monsoon by principal component analysis (PCA) in temporal domain (T-mode). The method utilizes the relationship of weekly rainfall activities with principal components (PCs) of southwest monsoon. Based on the relationships, subgroup of weeks with similar spatial patterns have been identified. Synoptic features of these subgroups have been brought out with the help of synoptic charts. The first four significant PCs are associated with four kinds of active phases of the southwest monsoon when the low pressure systems have typical characteristics corresponding to each PC. Thus, the study suggests a method of interpretation of PCs with the help of synoptic charts by objective identification of phases of southwest monsoon.